URGENSI KOMPETENSI MANAJERIAL KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU - Yumidar, Yumidar; Erwin, Erwin; Halisa, Nur; Kasmah, Kasmah (DIDAKTIKA, 2022)
This research is entitled about the managerial competence of madrasah principals in improving teacher performance at MTSN 1 Bone. The study was motivated by the important role of madrasah principals in improving teacher performance, implementing school quality as well as improving the quality of learning, because the movements of a school organization are controlled by a madrasah principal. This type of research uses a qualitative approach. Methods of data collection using interviews, observation and documentation. Data analysis used descriptive qualitative analysis, that qualitative research was carried out by collecting data in a reasonable condition. This research theoretically is able to contribute to the development of education management science, practically as information material in implementing the leadership management of madrasah principals in improving teacher performance. The results of this study indicate that in the context of managerial competence, the head of the MTSN 1 Bone madrasa is able to develop plans in order to improve teacher performance and develop the organization according to needs, the head of the madrasa creates a conducive climate to provide advice to teachers and employees and provide encouragement to teachers, has the right strategy to improve the performance of education staff teachers in madrasas in its implementation, researchers go directly to the field and try to collect complete data in accordance with problems related to implementation.